Development of Village-Owned Enterprises Business Strategy in South Misool, Raja Ampat Towards Village Economic Independence - Andi Sismar; Yoga Andriyan; Musriani Musriani; Hamsiah Hamsiah; Satria Lintang Rachmadana; Yusron Difinubun; Pahmi Pahmi; Sopian Sopian; Inri Aprilia Defrates; Williams Ishak Piet Samson; Ramles Rahakratat (Universitas Muhammadiyah Malang, 2025)
Development of Village-owned enterprises Business Strategy in South Misool, Raja Ampat Towards Village Economic Independence. Community service focuses on improving knowledge and business management skills for BUMDes managers. The purpose of community service is to encourage village economic independence, by creating a business strategy for Village-owned enterprises (BUMDes) in South Misool, Raja Ampat. The problems that occur include lack of management knowledge, difficulty in obtaining funds, and lack of marketing strategies. The implementation of community service to improve knowledge in Village-owned enterprises in South Misool, Raja Ampat is in the form of socialization and training using lecture, discussion and demonstration methods. The results of the Community Service obtained include: 1) The community knows how or models to develop coastal community-based businesses, 2) The community is able to implement marketing via social media or the internet, 3) The community through BUMDes is able to collaborate with the government and stakeholders in developing businesses in BUMDes in Kampung Misol Raja Ampat. This is a hope for village economic independence through increasing the capacity of BUMDes, increasing access to markets, and increasing the effectiveness of business management. One of the effects is increasing the welfare of village communities in South Misool and the creation of new jobs, which encourages economic growth.